PEMANFAATAN MESIN TETAS TELUR UNTUK PENINGKATAN SEKTOR PETERNAKAN DI DESA LALANG KABUPATEN BELITUNG TIMUR - Eka Sari Wijianti; Yudi Setiawan (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2015)
In the implementation of this Community Service Program (KKN), the main activities are focused on making egg hatching machines and utilizing these machines for chicken cultivation.Hatching chicken eggs using a hatching machine can be a quick way for the eggs to hatch. Without the help of a hatching machine, the process of eggs becoming chicks will take a long time and the risk of death is greater. For farmers, time is very valuable for the smooth running of the farm business, besides the success of hatching eggs is much greater than the manual method.The implementation of KKN is divided into 4 stages, the first stage is the manufacture of machines carried out before the implementation of KKN as well as the search for egg seeds. The second stage held a socialization on the use of egg hatching machines and how to breed chickens, the socialization was carried out by the East Belitung Regency Livestock Service Office. The third stage is making cages. Cages are made in the homes of lalang villagers who are selected based on an agreement from the village where the selected residents will then use the egg hatching machine to become chicken farmers. The fourth stage is chicken breeding, including feeding and vitamins. The last stage is monitoring, this stage is done to see how the chickens are developing before the KKN is completed.